Implementasi Desain Responsif untuk Website UMKM dengan Bootstrap 5.0 (Studi Kasus: Chovan Seserahan) - Febriyan, Salma Eka; Ningsih, Dewi Handayani Untari (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving digital economic growth in Indonesia. However, many MSME actors have yet to fully utilize website technology as a medium for promotion and customer interaction. Chovan Seserahan, an MSME engaged in wedding gift decoration services, faces challenges related to its website's lack of responsiveness across different devices. This study aims to design a responsive landing page by implementing the Bootstrap framework version 5.0. The research adopts the Research and Development (R&D) method, which includes stages of needs analysis, interface design, implementation, and evaluation through heuristic testing and user trials. Bootstrap was chosen due to its mobile-first approach and its provision of adaptive and efficient user interface components. The evaluation results show significant improvements in navigation comfort, page loading speed, and visual consistency across multiple devices. Heuristic testing conducted by three validators yielded a feasibility score of 95.76%, indicating that the design quality and user experience are in the “highly feasible” category. In addition, user feedback revealed a positive shift in content accessibility and presentation. These findings demonstrate that implementing a Bootstrap-based responsive design is effective in enhancing user interface quality and strengthening the digital presence of MSMEs. Therefore, this approach offers a strategic solution to support the sustainable digital transformation of MSMEs.